Effect of selected formal and legal factors on the quality of life of individuals with limited mobility. Study findings - Katarzyna Jaworska; Jakub Jan Zięty; Michał Krzykowski (Journal of Modern Science)
Objectives Within the framework of the research project entitled “Usefulness of a robotic companion in light of determinants affecting the quality of life of persons with limited mobility”, a survey was conducted among a group of 1,064 respondents aged at least 15 years. One of the objectives of the survey was to determine the subjective assessment of the impact of selected factors of a formal and legal nature on the quality of life of persons with limited mobility. T